South Sudan shutters all schools as it prepares for an extreme heat wave - Machol, Deng (AP News, 2024)
South Sudan’s government is closing down all schools starting Monday as the country prepares for a wave of extreme heat expected to last two weeks.
Keywords: _z:class:countries